PENINGKATAN KINERJA GURU DALAM MENETAPKAN KRITERIA KETUNTASAN MINIMAL MELALUI WORKSHOP DI SDN 091620 PERDAGANGAN - Marsal, Benni (Jurnal Tematik, 2020)
Improving Teacher Performance in Setting Minimum Completeness Criteria (KKM) Through Workshop at Sdn 091620 Trade. The purpose of this study was to improve the ability of teachers to set Minimum Completeness Criteria (KKM) through the implementation of workshops at SDN 091620 Perdaganga. This research is an action research, the subject of this research is the Principal and Teachers of State Elementary School 091620 Trade totaling 7 people, consisting of 1 principal and 6 class teachers. The teacher determines the Minimum Completeness Criteria. From the data analysis of the results of the observation and evaluation of the ability to compile the KKM skills in cycle I for the percentage of classical completeness achievement of 42.8% while in cycle II it becomes 100%; there is an increase of 19.96%. When viewed from the indicators performance for evaluation of the knowledge skills of teachers in compiling KKM can be said to be successful because it has reached the ideal percentage for absorption of 75 and completeness of 85%. Looking at the data above it can be said that the indicators of the expected / outcome variables and the action variables have been achieved. has been able to improve the ability of teachers-g uru at SD Negeri 091620 Perdagangan in analyzing and compiling KKM